Developing and Using a Multi-Criteria Framework to Assess Kazakhstan’s “Mother House” Project - Kholmatova, Dilbar; Tolebayeva, Marta (Nazarbayev University Graduate School of Public Policy, 2019)
The quality of services being delivered by the Mother House, a Non Governmental Fund which helps young women with newborn children under 1,5 years old, has never been evaluated before. This qualitative research fills the gap by generating a 10-dimensional Dependent Variable and identifying 5 Independent Variables that have a varying degree of influence on the quality of the Mother House operations. To the largest extent, the Mother House Project is successful in its agenda to tackle the phenomena of social orphanhood in Kazakhstan by preventing children to be placed in orphanages. However, the long-term capacity in funding might require the consideration of alternative strategies to maintain the sustainability of the project. The implications of this PAE are in bringing attention to the unique opportunities of private sector involvement in social services provision and in providing the reproducible assessment model which can potentially be incorporated into other social service facilities.